Perkembangan Desa Eks Transmigrasi Sejak 2003 hingga 2014 di Kabupaten Pelalawan - Syukran, Tengku Muhammad; Arisman, Defri; Faisal, Tengku Fazli; Marsita, Marsita; Maryati, Maryati; ROSALIZA, MITA (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2024)
Transmigration program in its development has become the strategy of developing villages. However, in some region, it occurs the decrease of transmigration performance. This study aimed to analyze development stadia of ex transmigration villages (the transmigration settlement after restoration) and to compare it with the development of non transmigration villages in Pelalawan District as well as to analyze factors which influence the development of ex transmigration villages in Pelalawan District.. The result of this study shows that (1) the development of ex transmigration villages is better than that of non transmigration villages, (2) percentage of ex transmigration villages in non farming industry supported by farming industry are increasing (3) easy access, road quality, longer transmigration settlement, and numbers of industries in the ex transmigration villages are factors which influence the ex transmigration villages to reach better village stadia